Edukasi Pengolahan dan Penanaman Tanaman Obat Keluarga sebagai Upaya Mengurangi Penyakit Hipertensi dan Asam Urat di Desa Curah Cottok, Situbondo - Made Indra Ayu Astarini; Ira Ayu Maryuti; Kristina Pae; Andrew Joewono (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Hypertension and gout are common among the elderly, negatively affecting their quality of life. Preventive measures are essential to avoid complications that may worsen with age. This community service activity aimed to educate the elderly on preventing hypertension and gout using family medicinal plants, such as roselle, butterfly pea flower, and bay leaves. The program took place on November 29–30, 2024, in Curah Cottok Village, Situbondo, using lectures, discussions, and hands-on practice in planting and processing herbal plants. Thirty-two participants, including elderly individuals and health volunteers, actively participated. The results showed an increased understanding among participants regarding the benefits of medicinal plants as a preventive measure for diseases. The program also encouraged the use of household land for growing herbal plants that are beneficial to health. This initiative is expected to enhance public awareness and foster self-reliance in maintaining health naturally and sustainably.